Experiencias subjetivas del ejercicio de poder en la vida consagrada de la Iglesia Católica - Arraya Solano, Evelyn Estefany (2022)
This research has its general objective to understand the subjective experiences of the exercise of power in the Consecrated Life of men and women religious congregations of the Catholic Church. Likewise, in this study, information was collected from participants who experienced feelings of guilt and submission to a normalized violent culture, which in many cases becomes part of daily life, getting used to an exercise of abusive power that remains entrenched within communities and is difficult to heal and restructure at an emotional level, as well as psychological, spiritual, and physical level. Such experiences revealed aspects such as clericalism's ecclesiopathy, hierarchical asymmetry, blind obedience, and conscience manipulation, as well as healthy experiences of power exercise that mark their vocational path and motivate men and women religious to maintain their hope in a power exercise that considers collective well-being.